Dermatoglyphics: A Forensic Tool to Predict Type 2 Diabetes Mellitus and Gender Identification among Kuwaiti Population: A Cross-Sectional Observational Study - Nishath Sayed Abdul; Teef Adel Gholoum; Latefah Abdulrahman Alali; Fatmah Tarahib Almuteri; Estabraq Osama Almeshal; Wadha Hassan Alsehali (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Type 2 diabetes mellitus, with increasing global prevalence and genetic influence, may be predicted using dermatoglyphics, a reliable forensic tool. This study evaluated dermatoglyphic patterns to identify type 2 diabetes in the Kuwaiti population. Materials and Methods: A cross-sectional observational study with 100 participants (50 diabetics, 50 controls) analysed fingerprint patterns (loops, whorls, arches). Results: 500 fingerprints were examined (250 diabetic, 250 control). Among diabetics, there were 21 males (42%) and 29 females (58%), while the control group included 20 males (40%) and 30 females (60%). The diabetic group showed a predominant loop pattern (48%), whereas the control group commonly exhibited the whorl pattern. Diabetic males mostly showed loops, and non-diabetic males showed whorls. Diabetic females had predominantly whorl patterns, while non-diabetic females showed loops. Conclusion: Loop patterns were more frequent in diabetics, while the whorls were common in non-diabetics, indicating predictive potential for type 2 diabetes.